Slavery, education, and inequality - Graziella Bertocchi; Arcangelo Dimico (Institute for the Study of Labor (IZA), 2010)
We investigate the impact of slavery on the current performances of the US economy. Over a cross section of counties, we find that the legacy of slavery does not affect current income per capita, but does affect current income inequality. In other words, those counties that displayed a higher proportion of slaves are currently not poorer, but more unequal. Moreover, we find that the impact of slavery on current income inequality is determined by racial inequality. We test three alternative channels of transmission between slavery and inequality: a land inequality theory, a racial discrimination theory and a human capital theory. We find support for the third theory, i. e., even after controlling for potential endogeneity, current inequality is primarily influenced by slavery through the unequal educational attainment of blacks and whites. To improve our understanding of the dynamics of racial inequality along the educational dimension, we complete our investigation by analyzing a panel dataset covering the 1940-2000 period at the state level. Consistently with our previous findings, we find that the educational racial gap significantly depends on the initial gap, which was indeed larger in the former slave states.
Keywords: E02; D02; H52; J15; O11; 330; slavery; development; inequality; institutions; education